2015
DOI: 10.3390/s150716557
|View full text |Cite
|
Sign up to set email alerts
|

A Vision-Based Sensor for Noncontact Structural Displacement Measurement

Abstract: Conventional displacement sensors have limitations in practical applications. This paper develops a vision sensor system for remote measurement of structural displacements. An advanced template matching algorithm, referred to as the upsampled cross correlation, is adopted and further developed into a software package for real-time displacement extraction from video images. By simply adjusting the upsampling factor, better subpixel resolution can be easily achieved to improve the measurement accuracy. The perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
234
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 340 publications
(237 citation statements)
references
References 33 publications
2
234
0
1
Order By: Relevance
“…Efforts have been spent on developing advanced vision-based systems to provide accurate and robust displacement measurement primarily of high-rise buildings, [8] short-span bridges, [9][10][11][12] and long-span bridges. [10,[13][14][15][16] Previous studies have indicated the significant potential of vision-based systems for structural condition evaluation, especially for system identification.…”
Section: Review Of Vision-based Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…Efforts have been spent on developing advanced vision-based systems to provide accurate and robust displacement measurement primarily of high-rise buildings, [8] short-span bridges, [9][10][11][12] and long-span bridges. [10,[13][14][15][16] Previous studies have indicated the significant potential of vision-based systems for structural condition evaluation, especially for system identification.…”
Section: Review Of Vision-based Approachesmentioning
confidence: 99%
“…• Correlation-based template matching is a classic and widely used technique, [8,9,13,14,16] which is realised by searching for an area in a new frame most closely resembling the reference (or template) that is predefined as a rectangular subset in the initial frame.…”
Section: Target Tracking Techniquesmentioning
confidence: 99%
See 3 more Smart Citations